BVRI Photometric Analysis and Spectra of the Dwarf Solar Type Algol Binary, V500 Pegasi. (24th April 2017) - Caton, Daniel B.; Samec, Ronald G.; Robb, Russell; Faulkner, Danny R.; Hamme, Walter Van; Clark, Jimmy D.; Shebs, Travis
Abstract: Observations and analyses of V500 Pegasi taken at the Dark Sky Observatory (DSO), the SARA North Observatory and the Dominion Astrophysical Observatory are presented. V500 Peg is an eclipsing binary with a period of 0.57983 d. The light curves have the appearance of a detached or semi-detached binary. Spectroscopy reveals that it is of F5V-type. A continuous 14-year period study may show an orbital period increase is occurring. This may be due to weak matter transfer with the primary component as the gainer. The light curve has a large difference in primary and secondary amplitudes that is typical of this class of binary. The final solution shows a total secondary eclipse. The solution is that of a classical Algol system (semi-detached with the secondary component filling its Roche lobe), but it is of solar type, with a magnetic spot. This may mean that magnetic braking is interfering in the nuclear evolution. The secondary component has a temperature of ∼4700 K (K3), which means it is somewhat overluminous for its mass.